Research ethics committees: agents of research policy? - Hemminki Elina (BMC, 2005)
Abstract The purpose of this commentary is to describe the unintended effects ethics committees may have on research and to analyse the regulatory and administrative problems of clinical trials. Discussion The Finnish law makes an arbitrary distinction between medical research and other health research, and the European Union's directive for good clinical trials further differentiates drug trials. The starting point of current rules is that clinical trials are lesser in the interest of patients and society than routine health care. However, commercial interests are not considered unethical. The contrasting procedures in research and normal health care may tempt physicians to continue introducing innovations into practice by relying on unsystematic and uncontrolled observations. Tedious and bureaucratic rules may lead to the disappearance of trials initiated by researchers. Trying to accommodate the special legislative requirements for new drug trials into more complex interventions may result in poor designs with unreliable results and increased costs. Meanwhile, current legal requirements may undermine the morale of ethics committee members. Conclusion The aims and the quality of the work of ethics committees should be evaluated, and a reformulation of the EU directive on good clinical trials is needed. Ethical judgement should consider the specific circumstance of each trial, and ethics committees should not foster poor research for legal reasons.